(3GdbQGAGJs - (3GHf NGdhjg , GdMSjf Hf CMeO Hf NGdhjg Hf MeOGf, CHh YHO Gddg,J (B370 (3g` s
(3ChdgG (B:s
(3gPG cJGH TQMJ aj bQGAGJ Cgd GdCeUGQ , hde jYO Pdc Edi eG jJUd HGdEYQGH ef JaSjQ eTcd s
(3NWhW eNJdaIs
(3CNQgG NW UOjb Hf YeQ Hf eMeO Hf GdMSfs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B175s
Keywords: (3GdbQGAGJ hGdJLhjOs